The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fonc.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban for Primary Prevention of Venous Thromboembolism in Patients With Multiple Myeloma Receiving Immunomodulatory Therapy

Abstract: Immunomodulatory drugs (IMiDs), including thalidomide, lenalidomide, and pomalidomide, have improved survival of patients with multiple myeloma (MM). However, these therapies are associated with an increased risk of venous thromboembolism (VTE). Apixaban has been approved for treatment of acute VTE and for risk reduction of recurrent VTE following initial therapy. In this phase IV single-arm study (NCT02958969), we aim to prospectively evaluate the safety and efficacy of apixaban for primary prevention of VTE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…There is an ongoing single-arm phase IV study (NCT02958969) that aims to evaluate prospectively the safety and efficacy of apixaban for primary VTE prevention in MM patients. The primary objective is to assess VTE occurrence within six months in patients who receive IMiD-based therapy [96]. At interim analysis at three months, no VTE events and no major hemorrhage was reported [96].…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing single-arm phase IV study (NCT02958969) that aims to evaluate prospectively the safety and efficacy of apixaban for primary VTE prevention in MM patients. The primary objective is to assess VTE occurrence within six months in patients who receive IMiD-based therapy [96]. At interim analysis at three months, no VTE events and no major hemorrhage was reported [96].…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
“…The primary objective is to assess VTE occurrence within six months in patients who receive IMiD-based therapy [96]. At interim analysis at three months, no VTE events and no major hemorrhage was reported [96]. Pergourie et al also recently presented data from the use of apixaban as prophylaxis in MM patients on IMiDs.…”
Section: Thromboprophylaxis: To Doac or Not To Doac?mentioning
confidence: 99%
“…LMWH or full dose warfarin with a target international ration of 2 - 3 is recommended for patients with ≥ 2 risk factors for VTE including advanced age, history of VTE, recent surgery, degree of disease burden, or combination steroid therapy [ 4 ]. Direct oral anticoagulants are not currently advised; however, there is an ongoing prospective randomized controlled trial of apixaban 2.5 mg twice daily versus to evaluate the rate of VTE in this population over 6 months [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have in fact shown a promising efficacy of the new oral anticoagulants (DOACs) in preventing thrombosis in cancer patients, including MM [40,49,51,55]. Recent studies also showed that apixaban, especially at low dose, was safe and effective for thromboprophylaxis in relatively small series of MM patients receiving an IMiD-containing regimen as first line treatment or for relapsed disease [53].…”
Section: Discussionmentioning
confidence: 99%
“…These recommendations were then taken up and confirmed by the 2015 European Myeloma Network (EMN) [ 38 ] and 2017 ESMO guidelines [ 39 ]. Limited data are available about thrombotic risk in patients on treatment with pomalidomie but, as with the other IMiDs, it seems to determine an increased risk of thrombosis [ 17 , 25 , 40 , 41 , 42 , 43 , 44 ]. With regard to the second-generation proteasome inhibitor Carfilzomib, phase III trial ASPIRE, which compares the efficacy of lenalidomide-dexamethasone versus carfilzomib-lenalidomide-dexamethasone, shows a higher incidence of VTE in the three-drugs arm (13% vs. 6%), despite the mandatory use of thromboprophylaxis [ 45 ].…”
Section: Introductionmentioning
confidence: 99%